Development Strategy of Edutourism Pantai Prestasi of Politeknik Pelayaran Banten - Kusharyanto Kusharyanto; Indah Purnaningratri; Muliawati Handayani; Fauzi Syahputra; Denta Tirtana (Berkala Perikanan Terubuk, 2023)
The BLU (Public Service Agency) higher education financial management system provides opportunities for agencies to manage and maximize assets for various activities within the scope of educational substance. The Banten Sailing Polytechnic's Achievement Beach Edutourism has been open since 2020 as an implementation of the SDGs goals to contribute to improving the quality of education, environmental protection and improving the community's economy. The development of edutourism located to the north of the campus area with a 1 km long landscape is expected to be able to support the preservation of the coastal environment and increase participation from the surrounding community. The aim of this research is to examine edutourism development strategies based on SWOT analysis. This research uses a survey and interview method, collection data includes primary data and secondary data. The study was carried out in a qualitative descriptive manner. Observations aspects include; assessing natural tourist objects and attractions, biological attractions, physical attractions, socio-cultural attractions, accessibility, socio-economic environmental conditions of communities around the area, management and services, accommodation, supporting facilities and infrastructure, relationships with tourist attractions in the area. surroundings and safety factors. Based on the SWOT analysis results of Banten Polytechnic Achievement Beach Eduwisata SWOT analysis, the development strategy is in quadrant I position which can be interpreted as meaning that this area has the potential to be developed more optimally. Achievement Beach Eduwisata has strengths and opportunities that can cover existing weaknesses and threats, so the development strategy should prioritize expand opportunities to become a new source of strength.